Mouse and Mole, fine feathered friends - Yee, Wong Herbert (Boston : Houghton Mifflin Books for Children, 2009)
When spring arrives, Mole and Mouse find a unique way to bird watch.
Keywords: Bird watching -- Fiction; Birds -- Fiction; Mice -- Fiction; Moles (Animals) -- Fiction; Spring -- Fiction